Kinerja UMKM di Kota Mataram : Peran Literasi Keuangan Literasi Digital Dukungan Pemerintah dan Kompetensi Sumber Daya Manusia - Yuli Astini; Agus Khazin Fauzi; Herawati Khotmi; Dara Intan Ariati (Indonesian Journal Publisher, 2025)
The purpose of this study was to examine the relationship between financial literacy, digital literacy, government support, and human resource competency on the performance of MSMEs in Mataram City. The population in this study were MSMEs spread across 6 sub-districts in Mataram City. In determining the minimum sample using the Slovin formula with the proportionate stratified sampling method and proportionate stratified random sampling used in determining the number of samples in each sub-district and distributing questionnaires. Multiple regression analysis was used as a testing tool in this study. The results of this study found that the variables of financial literacy, government support, and human resource competency did not significantly influence the performance of MSMEs in Mataram City, but the variable of digital literacy significantly influenced the performance of MSMEs in Mataram City.